Bidirectional Cause–Effect Relationship Between Urinary Interleukin-6 and Mood, Irritation, and Mental Activity in a Breast Cancer Survivor - Schubert, Christian; Hagen, Carmen (Frontiers in Neuroscience, 2018)
This ‘integrative single-case study’ (Schubert et al., 1999) investigated the bidirectional cause and effect relations between various emotional states (i.e. mood, irritation, mental activity) and urinary IL-6 levels in a 49-year-old female breast cancer survivor (woman) under conditions of ‘life as it is lived’. During a period of 28 days, the patient collected her entire urine in 12hour intervals for IL-6 measurement and completed each morning and evening a list of adjectives regarding mood, irritation and mental activity (55 measurements in total). Autoregressive integrated moving average modeling revealed a 4-day (circasemiseptan) cycle in the IL-6 time series. Furthermore, cross-correlational analyses after controlling for serial dependencies (significance level: p < 0.05) showed that worsening in mood and increases in irritation were followed by increases in urinary IL-6 levels with temporal delays between 12 and 36 h. In the opposite direction of effect, increases in urinary IL-6 levels were followed by elevations in mood and mental activity as well as decreases in irritation with temporal delays between 48 and 72 h. These results from cross-correlational analyses suggest that IL-6 may have a regulatory function in psychoneuroimmunological interplay and that, under certain conditions, IL-6 may be involved in health rather than sickness behavior. Moreover, the findings of this study are indicators of real-life negative feedback loops and are in line with psychoneuroimmunological research postulating complex brain-to-body-to-brain network-like structures.